Spectral Characterization and Charge – Transfer Complexes of Some Schiff Bases Derived from Aminopyridines and Hydroxyacetophenones - T.M. Al-Thib, Anwar; M. M. Al-Salhi, Muhammed (Iraqi Journal of Science, 2023)
The molecular structures of acetophenonylidine-4-aminopyridine (I), 2, 6-dihydroxyacetophenonlidine-4-aminopyridine (II), 2, 4, 6- trihydroxyaceto phenonylidine-4-aminopyridine (III) and 2, 6-dihydroxyacetophenonylidine-2-aminopyridine (IV) have been investigated by IR and UV-visible spectrophotometry. The IR data indicate that the hydroxyl groups of these Schiff bases exist as tautomeric mixtures of free and bonded with the azomethine groups. The electronic spectra, effect of polar and nonpolar solvents, and the effect of acidity and basicity on the electronic spectra were studied and discussed. Their charge-transfer (CT) complexes with chloranil in chloroform solvent were also investigated; these complexes absorb light at 398-533 nm. The ionization potentials of Schiff bases, the equilibrium constants , molar extinction coefficients of CT complexes and the dissociation energies of the complexes excited states were estimated and discussed, the values are 8.38 – 8.98 eV , 138 – 560 mol-1 dm3 , 530 – 1430 m2 mol-1 and 4.68 – 4.75 eV , respectively .